Resveratrol - its properties, occurrence and health benefits - Jabłońska, Wiktoria; Wardęszkiewicz, Marta; Kasprzak, Amelia; Markowiak, Szymon; Świercz, Maciej; Kubisz, Magdalena; Mańkowska, Aleksandra; Truchta, Monika; Pejas, Anna; Kolano, Agata (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Wine ingredients relevant to health are polyphenols, which are divided into flavonoids and non-flavonoids. Resveratrol is a non-flavonoid component of wine widely known for its health-promoting properties. This article will discuss its chemical structure, synthesis, metabolism, occurrence in nature and impact on human health. Review methods: The purpose of this article was to assemble and analyse the available data about resveratrol. The search of articles in Pubmed database was carried out using following keywords: “wine”, “resveratrol”, “polyphenols”, “alcohol”. Inclusion criteria: indexed in Pubmed database, published in last 10 years. Exclusion criteria: Case reports, studies in language other than English, studies that seemed to be biased. Descripiton of the state of knowledge: Resveratrol has a wide range of health-promoting effects. It inhibits some stages of platelet activation by reducing the synthesis of thromboxane A2 and their aggregation caused by agonists i.e. collagen, ADP, cathepsin G or thrombin. Furthermore, it causes a reduction in blood glucose and glycated hemoglobin levels, increases insulin sensitivity and potentially has protective effect on pancreatic cells. It lowers total plasma cholesterol and low-density lipoproteins levels while increasing insulin sensitivity and high-density lipoproteins level. In addition to this, it has neuroprotective, anti-tumour and anti-angiogenic effect proven in specific types of cancer. Summary: Resveratrol is said to improve the therapeutic outcome in patients suffering from cardiovascular diseases, diabetes type 2, Alzheimer's disease, other neurodegeneration diseases and in certain cancers. Nevertheless, the issue of resveratrol's effect on the human body requires further research.